Trading Justice for Peace? Reframing reconciliation in TRC processes in South Africa, Canada and Nordic countries - Henkeman, Stanley (AOSIS, 2021)
Conflict in its various manifestations continues to be a defining feature in many places throughout the world. In an attempt to address such conflict, various forms of a Truth and Reconciliation Commission (TRC) have been introduced to facilitate the transition from social conflict to a new dispensation. The introduction and subsequent proceedings of TRCs in South Africa, Canada and Norway are widely regarded as good examples of this approach. Against this background, a number of researchers from VID Specialized University and the University of the Western Cape had an exploratory meeting in Oslo in 2018 where the possibility for a joint research project under the broad theme of 'discourses on reconciliation' was first discussed. This led to two further research symposia in Cape Town and Tromsø in 2019. With the inclusion of specialists working on the Canadian Truth and Reconciliation process, these meetings demonstrated common ground and a shared understanding of the issues at stake. Moreover, it pointed to the differences between the South African, Canadian and Norwegian Commissions. In comparing the South African, Canadian and Norwegian experiences, researchers identified that these countries were, in fact, at different stages of their respective truth and reconciliation processes. This has prompted scholars to revisit and problematise these processes in relation to ongoing societal challenges. In all cases, it is quite apparent that reconciliation between individuals and groups remains a significant challenge.